2015
DOI: 10.1155/2015/687482
|View full text |Cite
|
Sign up to set email alerts
|

Primary Carcinoid Tumor of the Testis

Abstract: Primary carcinoid tumors of the testis are a rare entity comprising less than 1% of all testicular neoplasms. Their presence should be considered particularly when evaluating a testicular lesion in an older male patient. Immunohistochemical studies may aid in diagnosis and radiographic evaluation is important to rule out metastatic origin. Primary carcinoid tumors of the testis are associated with an excellent prognosis; however, surveillance is important given rare reports of delayed metastases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The survival rate of patients with primary testicular neuroendocrine tumor with lymph node and lung metastases can be increased with chemotherapy (cisplatin and etoposide; ifosfamide, epirubicin and octreotide), radiation therapy, etc. [8]. Some authors have reported that cisplatin-based chemotherapy regimens are the most useful to prevent tumor metastasis.…”
Section: E Granulosa Cell Tumormentioning
confidence: 99%
“…The survival rate of patients with primary testicular neuroendocrine tumor with lymph node and lung metastases can be increased with chemotherapy (cisplatin and etoposide; ifosfamide, epirubicin and octreotide), radiation therapy, etc. [8]. Some authors have reported that cisplatin-based chemotherapy regimens are the most useful to prevent tumor metastasis.…”
Section: E Granulosa Cell Tumormentioning
confidence: 99%